Recognize and Prevent Diabetes Mellitus with CERDIK at Mangunsari Health Center, Salatiga - Raswandaru, Marsela Riska; Karuhgair, Juan Christianto; Asyiqinnur, Ahmad; Khoirunnisa, Dian; Kulka, Gisteryana; Uropmabin, Tokon (Pascasarjana Universitas Mataram, 2024)
Diabetes mellitus is a chronic condition in which the body cannot produce or use insulin effectively, causing high blood sugar levels. Non-pharmacological therapy is one option to prevent and treat diabetes mellitus, for example